A structural hypothesis for the transition between bent and extended conformations of the leukocyte β2 integrins - Shi, Minlong (2008)
In this thesis, three fragments (PHE1, PHE2 and PHE3) of integrin beta2 subunit have been expressed and crystallized for structural and functional studies. The following solved crystal structures of the beta2 Genu in both bent (PHE2) and extended (PHE3) conformations provide a structural basis, represented by conformational changes located in the beta2 Genu.In addition, we showed that LFA-1 can be locked into a bent conformation by a disulfide bond strategically introduced between the PSI and I-EGF2 domains, the “bent” LFA-1 has the capacity for the ligand binding.